Evolutional and ecological implications of the properties of deep-sea barophilic bacteria - Yayanos, A. Aristides (Proc Natl Acad Sci U S A, 1986)
The rate of reproduction of deep-sea bacteria from six different capture depths between 1957 and 10,476 meters was studied as a function of temperature and pressure. The results showed the following: the true deep-sea bacteria of different depths have several characteristics, presumably evolutionally derived, distinguishing them from each other and from bacteria of atmospheric-pressure environments; pressure plays a significant role in determining the distribution of oceanic life; and pressure-adapted bacteria are easily recovered from and ubiquitous in the deep ocean. Organisms evolving in habitats of different temperatures and pressures need to be studied to understand the physical limits of life, the distribution of life within the earth and its oceans, the role of organisms in organic diagenesis and petroleum formation, and the possible existence of life on and within other planets.